2023
DOI: 10.3390/antiox12061174
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Opuntia spp. on Liver Health

Irene Besné-Eseverri,
Jenifer Trepiana,
Saioa Gómez-Zorita
et al.

Abstract: The genus Opuntia spp. includes plants capable of growing in arid, temperate and tropical climates. The vast majority of wild species grow in Mexico, but O. ficus-indica (prickly pear or nopal) is cultivated around the world and it is one of the most studied. This review shows the currently available knowledge concerning the action of O. ficus-indica and other Opuntia species (Opuntia vulgaris, Opuntia robusta, Opuntia streptacantha, Opuntia microdasys, Opuntia dillenii and Opuntia dejecta) on liver health. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The liver is an organ that plays a fundamental role in homeostasis and in maintaining various vital functions, such as fat and carbohydrate metabolism, bile excretion, regulation of the energy supply, and the ability to detoxify the body from endogenous and/or exogenous substances. However, these functions result in greater exposure and susceptibility to liver damage, considering that oxidative stress plays a crucial role in the etiopathogenesis of liver diseases [16,17]. In this context, including foods in the diet which can help maintain a healthy liver function is essential.…”
Section: Effects Of Cactus Consumption On Liver Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The liver is an organ that plays a fundamental role in homeostasis and in maintaining various vital functions, such as fat and carbohydrate metabolism, bile excretion, regulation of the energy supply, and the ability to detoxify the body from endogenous and/or exogenous substances. However, these functions result in greater exposure and susceptibility to liver damage, considering that oxidative stress plays a crucial role in the etiopathogenesis of liver diseases [16,17]. In this context, including foods in the diet which can help maintain a healthy liver function is essential.…”
Section: Effects Of Cactus Consumption On Liver Functionmentioning
confidence: 99%
“…Another point to consider is the protection against drug-induced damage [17]. These cacti have effects against damage induced by certain medications, such as paracetamol and carbon tetrachloride, in addition to the consumption of ethanol, which can be attributed to its antioxidant and anti-inflammatory properties [24][25][26].…”
Section: Effects Of Cactus Consumption On Liver Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…transaminases, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were lower in rats treated with Opuntia ficus-indica than in controls. Opuntia's antioxidant activity is of particular importance in the prevention and treatment of fatty liver (Besné-Eseverri et al, 2023).…”
Section: Serummentioning
confidence: 99%
“…For years, health benefits associated with the Opuntia genus have been documented in folk medicine, and this traditional knowledge remains highly relevant in many indigenous communities to this day [7]. From the scientific point of view, it has been observed that extracts of opuntioid cacti, obtained from fruits, cladodes or flowers, can exert beneficial properties for the prevention and treatment of certain disorders, such as obesity, type-2 diabetes, cardiovascular diseases, non-alcoholic fatty liver disease and several types of cancer [3,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%